Graphene modified composite fiber material and preparation process thereof

By combining graphene with aramid fiber and introducing synergistic agents and compatible crosslinking agents of titanium, boron and other elements, the problems of flame retardancy of nylon materials and graphene dispersion are solved, and graphene modified composites are significantly improved The flame retardant and mechanical properties of fiber materials optimize processing properties and durability.

CN119161728AInactive Publication Date: 2024-12-20LANDRED CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411689420.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Nylon materials perform poorly in flame retardancy, and the characteristics of graphene and nylon materials lead to compatibility and dispersion problems, limiting their application in flame retardant functional materials, and excessively high content of graphite Ethylene can cause the mechanical properties of the composite to decline.

Method used

By combining graphene with aramid fibers to form modified aramid fibers, and introducing synergistic agents and compatible crosslinking agents of elements such as titanium and boron, the process is optimized to improve the flame retardant properties of graphene modified composite fiber materials and Mechanical properties.

Benefits of technology

It significantly improves the mechanical properties and flame retardant properties of composite materials, optimizes processing properties, improves production efficiency and quality, and enhances the durability and application of composite fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of composite fiber materials, in particular to a graphene modified composite fiber material and a preparation process thereof. Comprising the following steps: step 1, (1) modifying graphene by using dopamine to obtain modified graphene; (2) further compounding the modified graphene with aramid fibers to obtain graphene modified aramid fibers; and 2, uniformly mixing the graphene modified aramid fiber, nylon, a flame-retardant synergist, a compatible cross-linking agent, azodiisobutyronitrile, isopropyl peroxide and an additive, and carrying out melt extrusion to obtain the graphene modified composite fiber material. The graphene-modified aramid fiber is used as a main flame-retardant component, the flame-retardant synergist is introduced for synergistic flame retardance, and the compatible cross-linking agent is introduced for effectively improving the dispersity and compatibility of the graphene-modified aramid fiber, so that the flame retardance is improved on the basis of effectively ensuring the mechanical properties of the graphene-modified composite fiber material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite fiber materials, and specifically to graphene-modified composite fiber materials and preparation processes thereof. Background Art

[0002] With the rapid development of the textile industry and the continuous improvement of consumer demand, the research and development of new fiber materials has become an important force to promote the progress of the industry. Nylon materials are widely favored for their good wear resistance, wrinkle resistance and moisture absorption; however, single nylon materials have poor performance in flame retardancy, which limits their application in flame retardant functional materials.

[0003] In the prior art, inorganic fillers such as graphene are usually used to improve the heat resistance and flame retardancy of nylon materials; however, the differences in properties between fillers such as graphene and nylon materials lead to compatibility and dispersibility problems between the two; therefore, in common processes, the content of graphene-like materials introduced is limited, and the improvement in flame retardancy is limited; on the other hand, too high a content of graphene materials will lead to a decrease in the mechanical properties of the composite material.

[0004] In summary, it is of great significance to prepare a graphene-modified composite fiber material. Summary of the invention

[0005] In view of the above problems existing in the prior art, the purpose of the present application is to provide a graphene-modified composite fiber material. Another purpose of the present application is to provide a preparation process of the graphene-modified composite fiber material.

[0006] In order to solve the above problems, the technical solutions adopted in this application are as follows: In a first aspect, the present application provides a process for preparing a graphene-modified composite fiber material, comprising the following steps: Step S1: adding graphene and dopamine hydrochloride into phosphate buffer, stirring and mixing at room temperature, washing and drying to obtain modified graphene; Step S2: adding modified graphene, 3-acryloyl dopamine, ethylenediamine, and aramid fiber into phosphate buffer, stirring and mixing at room temperature, washing, and drying to obtain graphene-modified aramid fiber; Step S3: Evenly mix the graphene-modified aramid fiber, nylon, flame retardant synergist, compatible crosslinking agent, azobisisobutyronitrile, isopropyl peroxide, and additives, and melt-extrude to obtain a graphene-modified composite fiber material.

[0007] In the first aspect of the present application, in step S3, the amount of each component is: by mass, 25 to 30 parts of graphene-modified aramid fiber, 55 to 60 parts of nylon, 4 to 5 parts of flame retardant synergist, 8 to 12 parts of compatible cross-linking agent, 0.05 to 0.1 parts of azobisisobutyronitrile, 0.05 to 0.1 parts of isopropyl peroxide, and 0.5 to 1 parts of additives; The additives include one or more of an antioxidant, a stabilizer, and a plasticizer.

[0008] In the first aspect of the present application, in step S2, the amount of each component is: 3 to 5 parts of modified graphene, 1 to 2 parts of 3-acryloyl dopamine, 0.5 to 1 part of ethylenediamine, and 2 to 3 parts of aramid fiber, by mass.

[0009] In the first aspect of the present application, in step S1, the amount of each component used is: 0.4-0.6 parts of graphene and 0.1-0.2 parts of dopamine hydrochloride, calculated by mass.

[0010] In the first aspect of the present application, the preparation method of the flame retardant synergist is: (1) Tetrabutyl titanate and 3-vinyl urushiol are added to xylene in sequence, reacted at 75-85°C for 1-2 hours, then the temperature is raised to 115-130°C and heated for 2-3 hours, and then the solvent is evaporated to obtain vinyl urushiol titanium; (2) Adding vinyl lacquer phenol titanium, mercaptoboric acid and azobisisobutyronitrile to DMF, reacting at 60-70° C. for 2-4 hours under ultraviolet light to obtain the flame retardant synergist.

[0011] In the first aspect of the present application, when preparing vinyl urushiol titanium, the amount of each raw material is: by mass, 2 to 3 parts of tetrabutyl titanate, 6 to 7 parts of 3-vinyl urushiol, and 40 to 50 parts of xylene; In the first aspect of the present application, when preparing the flame retardant synergist, the amount of each raw material is: by mass, 9-11 parts of vinyl lacquer phenol titanium, 4-5 parts of mercaptoboric acid, 0.5-1 part of azobisisobutyronitrile, and 40-50 parts of DMF.

[0012] In the first aspect of the present application, the preparation method of the compatible cross-linking agent is: (1) Mixing 80-85 wt % phosphoric acid aqueous solution and 35-40 wt % formaldehyde aqueous solution in a mass ratio of (1.5-3):(95-100) to obtain a phosphoric acid-formaldehyde mixed solution; adding nylon to the phosphoric acid-formaldehyde mixed solution in a solid-liquid ratio of 1:(15-18), and pretreating at 40-60° C. for 8-12 hours; washing and drying to obtain pretreated nylon; (2) Under a nitrogen atmosphere, pretreated nylon and mercaptosilane coupling agent are added to isopropanol in sequence, with the mass ratio of nylon to mercaptosilane coupling agent being 1:(2-4), followed by reaction at 60-80°C for 12-14 hours, washing and drying to obtain a compatible cross-linking agent.

[0013] In the first aspect of the present application, the raw materials in the compatible cross-linking agent include the following components, calculated by mass: 5 to 6 parts of pretreated nylon, 1 to 2 parts of mercaptosilane coupling agent, and 50 to 60 parts of isopropanol.

[0014] In a second aspect, the present application provides a graphene-modified composite fiber material prepared by the above process.

[0015] Compared with the prior art, the beneficial effects of this application are: 1. In this application, graphene is combined with aramid fiber to form modified aramid fiber, which can significantly improve the mechanical properties (such as tensile strength, modulus and toughness) of the composite material, while enhancing thermal stability and flame retardancy. In addition, the modification process also optimizes the processing performance of the composite material and improves production efficiency and quality.

[0016] 2. In the present application, by introducing synergists of elements such as titanium and boron, the flame retardant properties of the graphene-modified aramid fiber are effectively improved in coordination with the graphene-modified composite fiber material.

[0017] 3. In the present application, by introducing a compatible cross-linking agent and utilizing reaction compatibility, the mechanical properties of the graphene-modified composite fiber material are effectively improved, thereby enhancing the durability and applicability of the composite fiber. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme of the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the described embodiments of the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0019] For the purpose of the present application, it should be understood that, unless explicitly indicated otherwise, the present application may adopt various alternative changes and step sequences. In addition, except in any operating examples or otherwise specified, all numerical values ​​representing the amount of the composition used in the specification and claims should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the following specification and the appended claims are approximate values, which can vary according to the desired properties to be obtained by the present application. At least, it is not intended to limit the scope of the application of the doctrine of equivalents to the claims, and each numerical parameter should at least be interpreted according to the numerical value of the significant figures reported and by applying common rounding techniques.

[0020] Notwithstanding that the numerical ranges and parameters setting forth the broad scope of the disclosure are approximations, the numerical values ​​set forth in the specific examples are reported as precisely as possible. Any numerical value, however, inherently contains certain errors necessarily resulting from the standard deviation found in their respective testing measurements.

[0021] The following is a detailed introduction to this plan: The present invention provides a method for preparing a graphene-modified composite fiber material, comprising the following steps: Step S1: adding graphene and dopamine hydrochloride into phosphate buffer, stirring and mixing at room temperature, washing and drying to obtain modified graphene; Step S2: adding modified graphene, 3-acryloyl dopamine, ethylenediamine, and aramid fiber into phosphate buffer, stirring and mixing at room temperature, washing, and drying to obtain graphene-modified aramid fiber; Step S3: Evenly mix the graphene-modified aramid fiber, nylon, flame retardant synergist, compatible crosslinking agent, azobisisobutyronitrile, isopropyl peroxide, and additives, and melt-extrude to obtain a graphene-modified composite fiber material.

[0022] The additives include one or more of antioxidants, stabilizers, and plasticizers. Antioxidants include but are not limited to tri-(dipropylene glycol)-phosphite; stabilizers include but are not limited to polyvinyl alcohol; and plasticizers include but are not limited to dioctyl phthalate.

[0023] Among them, dopamine molecules are used to form hydrogen bonds with carboxyl groups on the surface of graphene through phenolic hydroxyl groups to achieve non-covalent bonding. Dopamine molecules undergo self-polymerization, and a polydopamine layer is formed through the reaction between amino groups and phenolic hydroxyl groups, which is further covered on the graphene surface. 3-acryloyl dopamine and ethylenediamine are copolymerized between modified graphene and aramid fiber to form a strong bonding material, which is graphene-modified aramid fiber.

[0024] Among them, the graphene-modified aramid fiber is obtained by the process of two dopamine copolymerizations. The compounding of dopamine materials improves the affinity with nylon and promotes the dispersion of graphene-modified aramid fiber; it can make the composite material easier to disperse and mix during the processing. This helps to improve the melt fluidity, extrusion stability and fiber continuity of the composite material, thereby improving processing efficiency and product quality.

[0025] In addition, compared with the introduction of modified graphene alone, the combination of graphene and aramid fiber can also promote the thermal decomposition and endothermic reaction inside the composite material; graphene-modified aramid fiber has better dispersibility and flame retardant properties.

[0026] The preparation method of the flame retardant synergist is: (1) Tetrabutyl titanate and 3-vinyl urushiol are added to xylene in sequence, reacted at 75-85°C for 1-2 hours, then the temperature is raised to 115-130°C and heated for 2-3 hours, and then the solvent is evaporated to obtain vinyl urushiol titanium; (2) Adding vinyl lacquer phenol titanium, mercaptoboric acid and azobisisobutyronitrile to DMF, reacting at 60-70° C. for 2-4 hours under ultraviolet light to obtain the flame retardant synergist.

[0027] In the scheme, a flame retardant synergist is introduced in the process of preparing the graphene-modified composite fiber material, which effectively enhances the flame retardancy of the graphene-modified composite fiber material while enhancing the thermal stability. Among them, the flame retardant synergist is a vinyl lacquer phenol titanium containing metal ions obtained by complexing the phenolic hydroxyl group in 3-vinyl lacquer phenol with titanium ions; and then the alkenyl group on its molecular chain is click-reacted with the mercapto boric acid to obtain it. Among them, the boron and titanium contained can effectively reduce heat, suppress smoke, effectively isolate and suppress combustion, and synergistically produce flame retardancy with graphene-modified aramid fiber.

[0028] The preparation method of the compatible cross-linking agent is: (1) Mixing 80-85 wt % phosphoric acid aqueous solution and 35-40 wt % formaldehyde aqueous solution in a mass ratio of (1.5-3):(95-100) to obtain a phosphoric acid-formaldehyde mixed solution; adding nylon to the phosphoric acid-formaldehyde mixed solution in a solid-liquid ratio of 1:(15-18), and pretreating at 40-60° C. for 8-12 hours; washing and drying to obtain pretreated nylon; (2) Under a nitrogen atmosphere, pretreated nylon and mercaptosilane coupling agent are added to isopropanol in sequence, with the mass ratio of nylon to mercaptosilane coupling agent being 1:(2-4), followed by reaction at 60-80°C for 12-14 hours, washing and drying to obtain a compatible cross-linking agent.

[0029] In the scheme, a compatible crosslinking agent is introduced, and the crosslinking of thiol and olefin groups is utilized to make the graphene-modified aramid fiber containing olefin groups crosslinked and dispersed in the graphene-modified composite fiber material. Among them, the compatible crosslinking agent is obtained by first hydroxylating and then thiolating nylon as the basis, and the reaction compatibility is utilized to effectively disperse the filler, thereby effectively ensuring the mechanical properties of the graphene-modified composite fiber material.

[0030] It should be noted that the following parts are by mass, and all raw material purchase manufacturers involved in this application are exemplified without any special restrictions: In the following embodiments, 3-acryloyl dopamine has a purity of 99%, CAS No. 201610-44-8, and is purchased from Hubei Xinkang Pharmaceutical Chemical Co., Ltd.; the aramid fiber is para-aramid, purchased from Ningxia Taihe Aramid Fiber Co., Ltd. Mercaptoboric acid is 3-mercaptophenylboric acid, CAS No. 352526-00-2; the model of mercaptosilane coupling agent is KH-580; the model of nylon is PA6; the additive is composed of tri-(dipropylene glycol)-phosphite, polyvinyl alcohol, and dioctyl phthalate in a mass ratio of 2:1.5:1.5.

[0031] Example 1 A preparation process of a graphene-modified composite fiber material comprises the following steps: Step 1: (1) 2.5 parts of tetrabutyl titanate and 6.5 parts of 3-vinyl urushiol are added to 45 parts of xylene in sequence, and the mixture is reacted at 80°C for 1.5 hours, and then the temperature is raised to 125°C and heated for 2.5 hours, and then the temperature is raised to 135°C and the solvent is evaporated to obtain vinyl urushiol titanium; (2) 10 parts of vinyl urushiol titanium, 4.5 parts of mercaptoboric acid and 0.8 parts of azobisisobutyronitrile are added to 45 parts of DMF in sequence, and the mixture is reacted at 65°C for 2 hours under ultraviolet light to obtain a flame retardant synergist; Step 2: (1) 83% phosphoric acid aqueous solution and 37% formaldehyde aqueous solution are mixed in a mass ratio of 1.8:98 to obtain a phosphoric acid-formaldehyde mixed solution; nylon is added to the phosphoric acid-formaldehyde mixed solution at a solid-liquid ratio of 1:17, and pretreated at 50°C for 10 hours; washed and dried to obtain pretreated nylon; (2) Under a nitrogen atmosphere, 5.5 parts of pretreated nylon and 1.5 parts of mercaptosilane coupling agent are added to 55 parts of isopropanol in sequence, with a mass ratio of nylon to mercaptosilane coupling agent of 1:3, and then reacted at 70°C for 13 hours, washed and dried to obtain a compatible cross-linking agent; Step 3: (1) Add 0.5 parts of graphene and 0.15 parts of dopamine hydrochloride to 55 parts of phosphate buffer at pH = 8.5, slowly stir at room temperature for 1.5 days, wash and dry to obtain modified graphene; (2) Add 4 parts of modified graphene, 1.5 parts of 3-acryloyl dopamine, 0.8 parts of ethylenediamine, and 2.5 parts of aramid fiber to 55 parts of phosphate buffer at pH = 8.5, slowly stir at room temperature for 1.5 days, wash to obtain graphene-modified aramid fiber; (3) Mix 28 parts of graphene-modified aramid fiber, 57 parts of nylon, 5 parts of flame retardant synergist, 10 parts of compatible cross-linking agent, 0.055 parts of azobisisobutyronitrile, 0.07 parts of isopropyl peroxide, and 0.8 parts of additives, and melt extrude at 250°C at a speed of 85 rpm to obtain a graphene-modified composite fiber material.

[0032] Example 2 A preparation process of a graphene-modified composite fiber material comprises the following steps: Step 1: (1) 2.5 parts of tetrabutyl titanate and 6.5 parts of 3-vinyl urushiol are added to 45 parts of xylene in sequence, and the mixture is reacted at 80°C for 1.5 hours, and then the temperature is raised to 125°C and heated for 2.5 hours, and then the temperature is raised to 135°C and the solvent is evaporated to obtain vinyl urushiol titanium; (2) 10 parts of vinyl urushiol titanium, 4.5 parts of mercaptoboric acid and 0.8 parts of azobisisobutyronitrile are added to 45 parts of DMF in sequence, and the mixture is reacted at 65°C for 2 hours under ultraviolet light to obtain a flame retardant synergist; Step 2: (1) 83% phosphoric acid aqueous solution and 37% formaldehyde aqueous solution are mixed in a mass ratio of 1.5:95 to obtain a phosphoric acid-formaldehyde mixed solution; nylon is added to the phosphoric acid-formaldehyde mixed solution at a solid-liquid ratio of 1:15, and pretreated at 40°C for 8 hours; washed and dried to obtain pretreated nylon; (2) Under a nitrogen atmosphere, 5 parts of pretreated nylon and 1 part of mercaptosilane coupling agent are added to 50 parts of isopropanol in sequence, with a mass ratio of nylon to mercaptosilane coupling agent of 1:2, and then reacted at 60°C for 12 hours, washed and dried to obtain a compatible crosslinking agent; Step 3: (1) Add 0.4 parts of graphene and 0.1 parts of dopamine hydrochloride to 50 parts of phosphate buffer at pH = 8.5, slowly stir at room temperature for 1 day, wash and dry to obtain modified graphene; (2) Add 3 parts of modified graphene, 1 part of 3-acryloyl dopamine, 0.5 parts of ethylenediamine, and 2 parts of aramid fiber to 50 parts of phosphate buffer at pH = 8.5, slowly stir at room temperature for 1 day, wash to obtain graphene-modified aramid fiber; (3) Mix 25 parts of graphene-modified aramid fiber, 60 parts of nylon, 5 parts of flame retardant synergist, 10 parts of compatible cross-linking agent, 0.05 parts of azobisisobutyronitrile, 0.05 parts of isopropyl peroxide, and 0.5 parts of additives, and melt extrude at 250°C at a speed of 85 rpm to obtain a graphene-modified composite fiber material.

[0033] Example 3 A preparation process of a graphene-modified composite fiber material comprises the following steps: Step 1: (1) 2.5 parts of tetrabutyl titanate and 6.5 parts of 3-vinyl urushiol are added to 45 parts of xylene in sequence, and the mixture is reacted at 80°C for 1.5 hours, and then the temperature is raised to 125°C and heated for 2.5 hours, and then the temperature is raised to 135°C and the solvent is evaporated to obtain vinyl urushiol titanium; (2) 10 parts of vinyl urushiol titanium, 4.5 parts of mercaptoboric acid and 0.8 parts of azobisisobutyronitrile are added to 45 parts of DMF in sequence, and the mixture is reacted at 65°C for 2 hours under ultraviolet light to obtain a flame retardant synergist; Step 2: (1) Mix 83% phosphoric acid aqueous solution and 37% formaldehyde aqueous solution in a mass ratio of 3:100 to obtain a phosphoric acid-formaldehyde mixed solution; add nylon to the phosphoric acid-formaldehyde mixed solution at a solid-to-liquid ratio of 1:18, and pretreat at 60°C for 12 hours; wash and dry to obtain pretreated nylon; (2) Under a nitrogen atmosphere, add 6 parts of pretreated nylon and 2 parts of mercaptosilane coupling agent to 60 parts of isopropanol in sequence, with a mass ratio of nylon to mercaptosilane coupling agent of 1:4, then react at 80°C for 14 hours, wash and dry to obtain a compatible crosslinking agent; Step 3: (1) Add 0.6 parts of graphene and 0.2 parts of dopamine hydrochloride to 60 parts of phosphate buffer at pH = 8.5, slowly stir at room temperature for 2 days, wash and dry to obtain modified graphene; (2) Add 5 parts of modified graphene, 2 parts of 3-acryloyl dopamine, 1 part of ethylenediamine, and 3 parts of aramid fiber to 60 parts of phosphate buffer at pH = 8.5, slowly stir at room temperature for 2 days, wash to obtain graphene-modified aramid fiber; (3) Mix 30 parts of graphene-modified aramid fiber, 55 parts of nylon, 4 parts of flame retardant synergist, 11 parts of compatible cross-linking agent, 0.1 parts of azobisisobutyronitrile, 0.1 parts of isopropyl peroxide, and 1 part of additive, and melt extrude at 250°C at a speed of 85 rpm to obtain a graphene-modified composite fiber material.

[0034] Comparative Example 1 Based on Example 1, the flame retardant coordinator is replaced by aluminum diethylphosphinate, and the other processes remain unchanged, specifically: Step 1: (1) 83% phosphoric acid aqueous solution and 37% formaldehyde aqueous solution are mixed in a mass ratio of 1.8:98 to obtain a phosphoric acid-formaldehyde mixed solution; nylon is added to the phosphoric acid-formaldehyde mixed solution at a solid-liquid ratio of 1:17, and pretreated at 50°C for 10 hours; washed and dried to obtain pretreated nylon; (2) Under a nitrogen atmosphere, 5.5 parts of pretreated nylon and 1.5 parts of mercaptosilane coupling agent are added to 55 parts of isopropanol in sequence, with a mass ratio of nylon to mercaptosilane coupling agent of 1:3, and then reacted at 70°C for 13 hours, washed and dried to obtain a compatible crosslinking agent; Step 2: (1) Add 0.5 parts of graphene and 0.15 parts of dopamine hydrochloride to 55 parts of phosphate buffer solution with a pH value of 8.5, slowly stir at room temperature for 1.5 days, wash and dry to obtain modified graphene; (2) Add 4 parts of modified graphene, 1.5 parts of 3-acryloyl dopamine, 0.8 parts of ethylenediamine and 2.5 parts of aramid fiber to 55 parts of phosphate buffer solution with a pH value of 8.5, slowly stir at room temperature for 1.5 days, wash and obtain graphene-modified aramid fiber; (3) Mix 28 parts of graphene-modified aramid fiber, 57 parts of nylon, 5 parts of aluminum diethylphosphinate, 10 parts of a compatible crosslinking agent, 0.055 parts of azobisisobutyronitrile, 0.07 parts of isopropyl peroxide and 0.8 parts of an additive, and melt extrude at 250°C at a speed of 85 rpm to obtain a graphene-modified composite fiber material.

[0035] Comparative Example 2 Based on Example 1, the compatible cross-linking agent is replaced by nylon, and the other processes remain unchanged, specifically: Step 1: (1) 2.5 parts of tetrabutyl titanate and 6.5 parts of 3-vinyl urushiol are added to 45 parts of xylene in sequence, and the mixture is reacted at 80°C for 1.5 hours, and then the temperature is raised to 125°C and heated for 2.5 hours, and then the temperature is raised to 135°C and the solvent is evaporated to obtain vinyl urushiol titanium; (2) 10 parts of vinyl urushiol titanium, 4.5 parts of mercaptoboric acid and 0.8 parts of azobisisobutyronitrile are added to 45 parts of DMF in sequence, and the mixture is reacted at 65°C for 2 hours under ultraviolet light to obtain a flame retardant synergist; Step 2: (1) Add 0.5 parts of graphene and 0.15 parts of dopamine hydrochloride to 55 parts of phosphate buffer solution with a pH value of 8.5, slowly stir at room temperature for 1.5 days, wash and dry to obtain modified graphene; (2) Add 4 parts of modified graphene, 1.5 parts of 3-acryloyl dopamine, 0.8 parts of ethylenediamine and 2.5 parts of aramid fiber to 55 parts of phosphate buffer solution with a pH value of 8.5, slowly stir at room temperature for 1.5 days, wash and obtain graphene-modified aramid fiber; (3) Mix 28 parts of graphene-modified aramid fiber, 67 parts of nylon, 5 parts of flame retardant synergist, 0.055 parts of azobisisobutyronitrile, 0.07 parts of isopropyl peroxide and 0.8 parts of additives, and melt extrude at 250°C at a speed of 85 rpm to obtain a graphene-modified composite fiber material.

[0036] Comparative Example 3 Based on Example 1, the graphene-modified aramid fiber is replaced by modified graphene, and the other processes remain unchanged, specifically: Step 1: (1) 2.5 parts of tetrabutyl titanate and 6.5 parts of 3-vinyl urushiol are added to 45 parts of xylene in sequence, and the mixture is reacted at 80°C for 1.5 hours, and then the temperature is raised to 125°C and heated for 2.5 hours, and then the temperature is raised to 135°C and the solvent is evaporated to obtain vinyl urushiol titanium; (2) 10 parts of vinyl urushiol titanium, 4.5 parts of mercaptoboric acid and 0.8 parts of azobisisobutyronitrile are added to 45 parts of DMF in sequence, and the mixture is reacted at 65°C for 2 hours under ultraviolet light to obtain a flame retardant synergist; Step 2: (1) 83% phosphoric acid aqueous solution and 37% formaldehyde aqueous solution are mixed in a mass ratio of 1.8:98 to obtain a phosphoric acid-formaldehyde mixed solution; nylon is added to the phosphoric acid-formaldehyde mixed solution at a solid-liquid ratio of 1:17, and pretreated at 50°C for 10 hours; washed and dried to obtain pretreated nylon; (2) Under a nitrogen atmosphere, 5.5 parts of pretreated nylon and 1.5 parts of mercaptosilane coupling agent are added to 55 parts of isopropanol in sequence, with a mass ratio of nylon to mercaptosilane coupling agent of 1:3, and then reacted at 70°C for 13 hours, washed and dried to obtain a compatible cross-linking agent; Step 3: (1) Add 0.5 parts of graphene and 0.15 parts of dopamine hydrochloride to 55 parts of phosphate buffer with a pH of 8.5, slowly stir at room temperature for 1.5 days, wash and dry to obtain modified graphene; (2) Mix 28 parts of modified graphene, 57 parts of nylon, 5 parts of flame retardant synergist, 10 parts of compatible cross-linking agent, 0.055 parts of azobisisobutyronitrile, 0.07 parts of isopropyl peroxide and 0.8 parts of additives, and melt extrude at 250°C at a speed of 85 rpm to obtain a graphene-modified composite fiber material.

[0037] Performance test: The graphene-modified composite fiber materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to relevant performance tests: (1) The flame retardancy of 130 mm × 6.5 mm × 3 mm specimens was tested using a JF-3 oxygen index meter; (2) The tensile strength was tested at a tensile rate of 2 mm / min; the obtained data are shown in Table 1.

[0038] Table 1 Performance test results

[0039] Result analysis: According to the data analysis in Table 1, it can be seen that the graphene-modified aramid fiber obtained by compounding graphene and aramid fiber is used as the main flame retardant, and a flame retardant synergist and a compatible cross-linking agent are further introduced; on the basis of effectively improving the flame retardancy of the graphene-modified composite fiber material, high mechanical properties are guaranteed.

Claims

1. A process for preparing a graphene-modified composite fiber material, characterized in that: The following steps are involved: Step S1: adding graphene and dopamine hydrochloride into phosphate buffer, stirring and mixing at room temperature, washing and drying to obtain modified graphene; Step S2: adding modified graphene, 3-acryloyl dopamine, ethylenediamine, and aramid fiber into phosphate buffer, stirring and mixing at room temperature, washing, and drying to obtain graphene-modified aramid fiber; Step S3: Evenly mix the graphene-modified aramid fiber, nylon, flame retardant synergist, compatible crosslinking agent, azobisisobutyronitrile, isopropyl peroxide, and additives, and melt-extrude to obtain a graphene-modified composite fiber material.

2. The preparation process of the graphene-modified composite fiber material according to claim 1, characterized in that: In step S3, the amount of each component is: by mass, 25-30 parts of graphene-modified aramid fiber, 55-60 parts of nylon, 4-5 parts of flame retardant synergist, 8-12 parts of compatible cross-linking agent, 0.05-0.1 parts of azobisisobutyronitrile, 0.05-0.1 parts of isopropyl peroxide, and 0.5-1 parts of additives; The additives include one or more of an antioxidant, a stabilizer, and a plasticizer.

3. The preparation process of the graphene-modified composite fiber material according to claim 1, characterized in that: In step S2, the amount of each component is: 3 to 5 parts of modified graphene, 1 to 2 parts of 3-acryloyl dopamine, 0.5 to 1 part of ethylenediamine, and 2 to 3 parts of aramid fiber, by mass.

4. The preparation process of the graphene-modified composite fiber material according to claim 1, characterized in that: In step S1, the amount of each component used is: 0.4-0.6 parts of graphene and 0.1-0.2 parts of dopamine hydrochloride, by mass.

5. The preparation process of the graphene-modified composite fiber material according to claim 1, characterized in that: The preparation method of the flame retardant synergist is: (1) Tetrabutyl titanate and 3-vinyl urushiol are added to xylene in sequence, reacted at 75-85°C for 1-2 hours, then the temperature is raised to 115-130°C and heated for 2-3 hours, and then the solvent is evaporated to obtain vinyl urushiol titanium; (2) Adding vinyl lacquer phenol titanium, mercaptoboric acid and azobisisobutyronitrile to DMF, reacting at 60-70° C. for 2-4 hours under ultraviolet light to obtain the flame retardant synergist.

6. The preparation process of the graphene-modified composite fiber material according to claim 5, characterized in that: When preparing vinyl lacquer phenol titanium, the amount of each raw material used is: 2-3 parts of tetrabutyl titanate, 6-7 parts of 3-vinyl lacquer phenol, and 40-50 parts of xylene, calculated by mass.

7. The preparation process of the graphene-modified composite fiber material according to claim 5, characterized in that: When preparing the flame retardant synergist, the amount of each raw material is: by weight, 9-11 parts of vinyl lacquer phenol titanium, 4-5 parts of mercaptoboric acid, 0.5-1 part of azobisisobutyronitrile, and 40-50 parts of DMF.

8. The process for preparing the graphene-modified composite fiber material according to claim 1, characterized in that: The preparation method of the compatible cross-linking agent is: (1) mixing 80-85 wt % of a phosphoric acid aqueous solution and 35-40 wt % of a formaldehyde aqueous solution in a mass ratio of (1.5-3):(95-100) to obtain a phosphoric acid-formaldehyde mixed solution; Add nylon to a phosphoric acid-formaldehyde mixed solution with a solid-liquid ratio of 1:(15-18), pretreat at 40-60°C for 8-12 hours; wash and dry to obtain pretreated nylon; (2) Under a nitrogen atmosphere, pretreated nylon and mercaptosilane coupling agent are added to isopropanol in sequence, with the mass ratio of nylon to mercaptosilane coupling agent being 1:(2-4), followed by reaction at 60-80°C for 12-14 hours, washing and drying to obtain a compatible cross-linking agent.

9. The process for preparing the graphene-modified composite fiber material according to claim 8, characterized in that: The raw materials in the compatible cross-linking agent include the following components, calculated by weight: 5-6 parts of pretreated nylon, 1-2 parts of mercaptosilane coupling agent, and 50-60 parts of isopropanol.

10. The graphene-modified composite fiber material prepared by the process according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for grafting modified aramid fiber on surface of graphene oxide

    CN104047160A

  • Poly dopamine-modified reduced graphene oxide and preparation method and application thereof

    CN104399090A

  • Method for performing amino functionalizing on carbon fiber surface

    CN105113260A

  • Surface modified aramid fiber and preparation method thereof

    CN105603717A

  • Novel rubber compound stuffing preparing method based on mercapto-alkene chemical reaction

    CN105778156A